EMISI GAS FORMALDEHIDA PAPAN PARTIKEL DARI BEBERAPA JENIS KAYU - Rozak Memed (Jurnal Penelitian Hasil Hutan, 1987)
The result of determination of formaldehyde emission from particleboard samples glued  with urea formaldehyde and mixture  of UF and MF resin is reported in this paper. The particleboard  samples were selected from two different factories  in addition  to  those prepared  in the laboratory  at the center.The  values of formaldehyde emission  of particleboard  prepared  in the laboratory  are between 6.154 ppm (Jeungjing)  and  18.720 ppm (meranti kuning), from  factory  A between  0.295  ppm-7.710 ppm;  while from  factory  B between  13.246 ppm-23.691 ppm.  Board samples from factory A glued with mixture of  UF and MF  resins.  on the other  hand,  show an average emission  value of  0.295 ppm.